PEMBUATAN INSTRUMEN EVALUASI PEMBELAJARAN IPA TERPADU BERBASIS ICT UNTUK MENGUKUR KOMPETENSI SISWA SMP KELAS VIII - Hasanatun Ma’muroh (PILLAR OF PHYSICS EDUCATION, 2014)
Learning science which is done in integrated learning in junior high school level requires an evaluation instrument in accordance with the evaluation standard and based on ICT. Evaluation Instrument of integrated science based on ICT teaching is not yet available in the schools. One solution that can be done to overcome this problem is to make evaluation instrument of integrated science learning based on ICT in accordance with the authentic assessment guidelines. The use of evaluation instrument in integrated science based on ICT is expected to make the assessment proces more interactive, interesting and fun. The purpose of this research is to produce an evaluation instrument of integrated science learning based on ICT which is valid, practice, and effective. The type of research is Research and Development. Research design which is used for limited test is before and after experiment design. There are two kinds of object research, those are evaluation instruments of integrated science learning based on ICT and eighth grade students. The instruments are used to collect data are validity sheet, practicality sheet, and learning outcomes test sheet. Based on analyze of data, there are two results of this research. First, evaluation instrument of integrated science based on ICT has high validity with an average score of 85,24. The design of evaluation instrument of integrated science based on ICT has home, introduction, blue print, instrument, download, and additional menu such as chat and discussion forum. Second, the value of practicallity of worksheet by teachers and students each are 84,44 and 83,17. The Evaluation instrument of integrated science based on ICT is effective to increase learning outcomes of students